Pengaruh Kapasitas Sumber Daya Manusia Dan Pemanfaatan Teknologi Informasi Terhadap Ketepatwaktuan Laporan Keuangan Nagari (Studi Kasus Kantor Wali Nagari Sarik Alahan Tigo) - Magdalena, Maria; Sixmi, Walisa (JURNAL PUNDI, 2021)
Fast traslate Icon translate This research aims to test the influence of human resources Capacity and utilization of information technology on the timeliness of financial reporting village. This is a quantitative research. Population on this research are all employee in Sarik Alahan Tigo Village. Total sampling are used as the sampling method with 34 respondents. The data  used on this research are Primary Data, collected with a direct survey using questionnaire that sent to employeeWali Nagari Sarik Alahan Tigo. Multiple Linear Regression analysis are used as analysis method with using SPSS Version 16 as the tools.The results showed that thepartially human resources Capacity had a positive and significant effect on the timeliness of financial reporting village and utilization of information technology havepositive and significant effect on the timeliness of financial reporting village